THE USE OF VIRTUAL LABORATORY OF ACID-BASE MATERIALS TO IMPROVE STUDENTS LEARNING OUTCOME - Rohaeni Nur Eli; Raniutami Widiyanti (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2020)
This study aimed to determine how much animation-assisted learning can improve students’ learning outcomes in chemistry subjects, especially acid-base solution. This research is a type of classroom action research. Research subjects are 33 students of 2th Vocational High School Cimahi grade X Multimedia C on the academic year 2019-2020. Data collection techniques using written test questions, questionnaires, and observations. The method of classroom action research is taken in two cycles. Each cycle has four stages, which consist of planning, implementation, observation, and reflection. This class of research took place from September 2019 to December 2019. The percentage of class learning completeness obtained through written tests in the first cycle was 72.73% (74.55% class average) and 87.87% for the second cycle (average grade 77.57%). Thus, it can be concluded that the use of animation can improve student learning outcomes in chemistry subjects in acid-base solutions.